Brain Network Convergence of Abnormal Gray Matter and Functional Activity of Pathological Dissociative Symptoms - Xuhan Cui; Leyi Zhang; Yangpan Ou; Yong Liu; Bing Lang; Wenbin Guo (Psychiatry and Clinical Neurosciences, 2026)
Aim Pathological dissociation is a complex clinical symptom widely observed across various psychiatric disorders. Dissociative symptoms prolong the duration of hospitalization and are associated with a poor clinical prognosis. Although several pathological models (e.g., the frontal‐limbic overmodulation model and the defense cascade model) have been proposed to interpret dissociative symptoms, heterogeneous regional‐level imaging findings impede our comprehension of the neural changes underlying dissociative symptoms across diagnoses. Methods Using the functional connectivity network mapping method, this study systematically screened 45 cross‐diagnostic reports of dissociation‐related structural and functional brain changes. By integrating resting‐state imaging data from healthy individuals ( n = 872), we constructed dissociative task‐induced activation, gray matter volume (GMV), and resting‐state activity impairment networks. Additionally, we performed spatial correlation analyses between the damage networks and 19 neurotransmitter distribution maps. Results The task‐induced damage network showed the largest proportional overlap with the anterior salience network (SN, 12.25%), basal ganglia network (BGN, 13.57%), and dorsal default mode network (DMN, 17.74%). For the GMV damage network, the main overlap proportions were observed with the dorsal DMN (12.33%) and the anterior SN (7.67%). The resting‐state activity damage network showed the greatest overlap with the anterior SN (5.17%), posterior SN (5.73%), auditory (5.47%), and sensorimotor network (4.50%). Spatial correlation analyses found associations between network changes and the distribution of N‐methyl‐D‐aspartate receptors, vesicular acetylcholine transporter, cannabinoid receptor CB1, serotonin transporter, and mu‐opioid receptor. Conclusion This study further elucidated the neuroimaging changes underlying across‐diagnostic dissociation and provided new insights for identifying network intervention targets to improve dissociative symptoms.